The Root Tile Design for Level 1 Cache for Non Uniform Architecture - Dr. Manjudevi, Suma Sannamani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
NUCA has become solution for wire delay problems, where wire delay problems increases on chip latency in multiprocessor system. Non uniform architecture is used for cache memory. Here cache is divided into tiles ,each tiled cache is accessed with different latency. Hence it is called non uniform. Access data defines search algorithm across architecture. This paper involves design of root tiles which accepts request from processor and forward request to child cache tiles. Here we have used Xilinx simulation tool to analyze the performance.